Carbon footprint reduction potential for diesel-fuelled generators through periodic maintenance using EXORIN treatment - Alimin, Ahmad Jais; Asmat, Fatina; Lee, Clement Nyuk Yin; Subramaniyan, S. Kanna; Osman, Shahrul Azmir; Razali, Mohd Azahari (2024)
Climate change and greenhouse gas emissions are among the most pressing global issues, with reduction of carbon footprint has been identified as one of the main indicators in this battle. In the effort to reduce carbon footprint generation, a local power utility company, located in East Malaysia that operates diesel-fuelled generators had conducted a periodic maintenance program using EXORIN treatment. EXORIN treatment program focused on improving the fuelling capability of the diesel-fuelled generators. Using comparative tests from untreated and treated operations, the carbon footprint emission levels were determined by comparing data obtained from gaseous emission sampling method, dark smoke observation and data of stationary source from the utility powerplant. From analysed data, CO and CO2 emissions were successfully reduced by around 7%. The combustion and energy efficiencies had also improved within the range of 9% to 21%. Fuel economy, which is dependent on the consumers electricity demands, also showed significant trend. These results outlined the potential of reducing carbon footprint using the dedicated EXORIN treatment program